2010
DOI: 10.1086/644750
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Individual Choices in Group Settings: The Long and Winding (Less Traveled) Road?

Abstract: This study revisits Ariely and Levav's previous findings in relation to consumers' need for variety when ordering (food or beverages) in a group setting. We examine how group opinion and unanimity can explain consumers' individual choice in a group setting. We hypothesize that the relationship between individual choice and group opinion is nonmonotonic as it is moderated by the degree of unanimity around an alternative. We demonstrate this effect in two empirical studies. We show that choice patterns are curvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…This is pertinent in the given context, because of the inferential consequences of the two types of pride -getting along with versus getting ahead of others. Ariely and Levav (2000) demonstrated that the salience of in-group members' choices leads to uniqueness-seeking (insofar as ones dining partners are ingroup members), but Quester and Steyer (2010) then showed that the effect is actually not linear, This is the Pre-Published Version but in fact much more complex. Hence, returning to our opening vignette, Pia's choice of cocktail versus microbrew might depend not just on how she attributes her pride based on her lay theories, but be further qualified by how she relates that pride to her colleagues in the product launch team.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This is pertinent in the given context, because of the inferential consequences of the two types of pride -getting along with versus getting ahead of others. Ariely and Levav (2000) demonstrated that the salience of in-group members' choices leads to uniqueness-seeking (insofar as ones dining partners are ingroup members), but Quester and Steyer (2010) then showed that the effect is actually not linear, This is the Pre-Published Version but in fact much more complex. Hence, returning to our opening vignette, Pia's choice of cocktail versus microbrew might depend not just on how she attributes her pride based on her lay theories, but be further qualified by how she relates that pride to her colleagues in the product launch team.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, the choices of others do not always result in consumers internalizing the social presence's option. Rather, in the context of food choices, various characteristics related to the social presence such as appearance (e.g., McFerran, Dahl, Fitzsimons, & Morales, ) and social number (Quester & Steyer, ), can lead to divergent choice behaviors. For example: when deciding how much food to select, a consumer may use a social presence's food quantity decision as information to establish an anchor, but the social presence's body type (i.e., obese vs. thin) as information in adjustment decisions.…”
Section: Three Types Of Social Influencementioning
confidence: 99%
“…These items become part of the extended self, and can be used to satisfy psychological needs, such as reinforcing and expressing self-identity, and allowing one to differentiate oneself and assert one's individuality (e.g., Ball & Tasaki, 1992;Belk, 1988;Kleine, Kleine, & Allen, 1995). Possessions can also serve a social purpose by reflecting social ties to one's family, community, and/or cultural groups, including brand communities (Muniz &O'Guinn, 2001;Escalas&Bettman, 2005;Algesheimer, Dholakia& Herrmann, 2005). Products can signal our status (Wang &Griskevicius, 2014), our individuality (Quester&Steyer, 2010;White, Simpson, & Argo, 2014), or our relationships (Fuchs, Schreier, & van Osselaer, 2015).…”
Section: Social Identitymentioning
confidence: 99%